2012
DOI: 10.1002/art.33445
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of subchondral bone osteoblast metabolism by cyclic compression

Abstract: Objective. Recent data have shown that abnormal subchondral bone remodeling plays an important role in osteoarthritis (OA) onset and progression, and it was suggested that abnormal mechanical pressure applied to the articulation was responsible for these metabolic changes. This study was undertaken to evaluate the effects of cyclic compression on osteoblasts from OA subchondral bone.Methods. Osteoblasts were isolated from sclerotic and nonsclerotic areas of human OA subchondral bone. After 28 days, the osteobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 52 publications
(68 reference statements)
1
81
0
4
Order By: Relevance
“…Increased Cx43 in osteoarthritic joints has biological plausibility considering that increased mechanical load can lead to both the degradation of joints and an increase in Cx43. 15,42 This might support treatment protocols aimed at reducing stress at the glenohumeral joint.…”
Section: Discussionmentioning
confidence: 86%
“…Increased Cx43 in osteoarthritic joints has biological plausibility considering that increased mechanical load can lead to both the degradation of joints and an increase in Cx43. 15,42 This might support treatment protocols aimed at reducing stress at the glenohumeral joint.…”
Section: Discussionmentioning
confidence: 86%
“…Recent data support the view that cartilage and bone do communicate over the calcified tissue barrier through molecular crosstalk. This interaction is crucial for the subchondral bone-articular cartilage unit and seems to show specific changes in the development of OA [25][26][27]. Currently it is not clear whether subchondral bone changes occur as cause or consequence of cartilage damage.…”
Section: Bone and Cartilagementioning
confidence: 95%
“…Further, under basal conditions, OA osteoblasts produce more insulinlike growth factor-1 and urokinase than normal cells. It has also been reported that subchondral bone explants from OA patients produce more IL-6, IL-8, and MMP-13 (154) as well as osteopontin, osteocalcin, TGF-β1, type I collagen, IL-6, IL-8, and high levels of alkaline phosphatase (ALP) but downregulated osteoprotegerin (OPG) gene expression and protein production (155)(156)(157). IL-6 and PGE2 stimulate receptor activator of nuclear factor Kappa-B-/Ligand (RANKL) and inhibit OPG production by osteoblasts and thus increase osteoclast differentiation and activation via their effect on the RANK/RANKL/OPG system (158,159).…”
Section: Subchondral Osteoblasts Have An Abnormal Phenotype In Oamentioning
confidence: 98%